2019
DOI: 10.1021/acs.jced.9b00593
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Acetoguanamine in Twelve Neat Solvents from 283.15 to 323.15 K

Abstract: By using the shake-flask method, the acetoguanamine solubilities in water, acetonitrile, methanol, n-butanol, isopropanol, isobutanol, ethanol, n-propanol, N,N-dimethylformamide (DMF), 1,4-dioxane, ethyl acetate, and ethylene glycol (EG) were acquired over the temperatures from 283.15 to 323.15 K at ambient pressure (p = 101.2 kPa). The mole fraction of acetoguanamine in equilibrated liquor increased as the temperature increased and followed the order in different solvents: DMF > EG > ethyl acetate > 1,4-dioxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…From Figure (c) and Table , the solubility order in the polar aprotic solvents was inconsistent with the sequences of solubility parameter, polarity, dipole moment, and dielectric constant. This indicated that the dissolution equilibrium of moroxydine hydrochloride was a complex phenomenon in the polar aprotic solvents which may be attributed to multi-influence factors, for instance, solvent properties, molecular sizes and shapes, steric effect, the interactions of solute–solvent, solvent–solvent, and solute–solute, etc. In addition, intersects between the solubility curves in polar aprotic solvents were found in Figure (c). This may be caused by the weight differences of the above factors at different temperatures. , …”
Section: Resultsmentioning
confidence: 93%
“…From Figure (c) and Table , the solubility order in the polar aprotic solvents was inconsistent with the sequences of solubility parameter, polarity, dipole moment, and dielectric constant. This indicated that the dissolution equilibrium of moroxydine hydrochloride was a complex phenomenon in the polar aprotic solvents which may be attributed to multi-influence factors, for instance, solvent properties, molecular sizes and shapes, steric effect, the interactions of solute–solvent, solvent–solvent, and solute–solute, etc. In addition, intersects between the solubility curves in polar aprotic solvents were found in Figure (c). This may be caused by the weight differences of the above factors at different temperatures. , …”
Section: Resultsmentioning
confidence: 93%
“…In addition, although the solubility of l -alanine in polar protic solvents was higher than that in polar aprotic solvents, the order in the two kinds of solvents was both inconsistent with the polarity, dipole moment, dielectric constant, and solubility parameter orders (the solvent properties can be seen in Table ). This indicated that the dissolution equilibrium of l -alanine was a complex phenomenon, which may be attributed to the comprehensive influence of various factors, such as solvent properties, molecular sizes and shapes, solute–solvent interactions, solvent–solvent interactions, solute–solute interactions, steric effect, etc. From Figure b, there were some intersects between the solubility curves, which may result from the weight differences of the above factors under different temperatures. , …”
Section: Resultsmentioning
confidence: 95%